Methanol production via CO2 hydrogenation reaction: Effect of catalyst support - Tasfy, S. (Inderscience Enterprises Ltd., 2017)
In this project, Cu-based catalyst was synthesised via impregnation method on various supports such as Al2O3, Al2O3-ZrO2, SBA-15 and Al-modified SBA-15. Samples were characterised by N2 adsorption-desorption, field-emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), temperature-programmed desorption/reduction (TPD/R) and pulse chemisorption. The activity of the supported Cu-based catalyst was evaluated in a fixed-bed micro-reactor at 483 K, 2.25 MPa, and H2/CO2 ratio of 3:1. Our results showed that the nature of the oxide support influenced the physicochemical properties of the catalysts as well as the catalytic activity and product selectivity. The size of catalyst nanoparticles ranged from 9 nm to 37 nm, depending on the type of support used. The Cu-based catalyst supported on SBA-15 resulted in 13.96 CO2 conversion and methanol selectivity of 91.32 and these values were higher than those obtained using Cu-based catalyst supported on other oxide carriers. Copyright © 2017 Inderscience Enterprises Ltd.